2016
DOI: 10.1534/g3.116.030882
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Bound GeneSwitch Causes Developmental Aberrations inDrosophilathat Are Alleviated by the Alternative Oxidase

Abstract: Culture of Drosophila expressing the steroid-dependent GeneSwitch transcriptional activator under the control of the ubiquitous α-tubulin promoter was found to produce extensive pupal lethality, as well as a range of dysmorphic adult phenotypes, in the presence of high concentrations of the inducing drug RU486. Prominent among these was cleft thorax, seen previously in flies bearing mutant alleles of the nuclear receptor Ultraspiracle and many other mutants, as well as notched wings, leg malformations, and bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Heat production by mitochondrial uncoupling is to date only detectable in AOX-expressing cells in the presence of antimycin A 32 , but the lowering of ROS apparently occurs even under normal physiological conditions when OXPHOS is properly functioning, at least in adult flies 33 . In addition, the fact that AOX can rescue developmental defects not related, a priori , to mitochondrial dysfunction, such as cleft thorax, notched wings, leg malformations, and bristle abnormalities in Drosophila 20 , indicates that yet unknown cellular mechanism(s) is(are) operating when AOX is present in the mitochondria of higher animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat production by mitochondrial uncoupling is to date only detectable in AOX-expressing cells in the presence of antimycin A 32 , but the lowering of ROS apparently occurs even under normal physiological conditions when OXPHOS is properly functioning, at least in adult flies 33 . In addition, the fact that AOX can rescue developmental defects not related, a priori , to mitochondrial dysfunction, such as cleft thorax, notched wings, leg malformations, and bristle abnormalities in Drosophila 20 , indicates that yet unknown cellular mechanism(s) is(are) operating when AOX is present in the mitochondria of higher animals.…”
Section: Discussionmentioning
confidence: 99%
“…AOX function has also been reported to provide some benefit in other models of mitochondrial disorders, such as fly lines with knockdown of pol γ 17 or with mutations in dj-1β , the homologue of the human Parkinson’s disease gene DJ1 12 , and in sesB , the homologue of another PEO gene, ANT1 18 . In addition, the rescue by AOX of Drosophila models of Alzheimer’s disease and mid-line closure defects suggests that RC dysfunction and/or excess ROS production are not only involved, but also appear in early stages of these pathogeneses 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AOX from Ciona intestinalis showed rescuing of various pathological symptoms in fruit flies with modelled Alzheimer disease (El-Khoury et al, 2016). As mentioned above, AOX was surprisingly able to rescue developmental abnormalities related to thoracic closure in fruit fly (Andjelković et al, 2016). It is also planned to apply AOX towards ischemia injuries (Rustin and Jacobs, 2009;Mills et al, 2016).…”
Section: By-passing Defects In Canonical Rs Complexesmentioning
confidence: 99%
“…Thus during regeneration, NDH2 and AOX would enable oxidation of reducing equivalents formed in Krebs cycle in maturating mitochondria. Reports on the involvement of AOX in development, particularly in apoptosis and cellular differentiation, were recently published (Andjelković et al, 2016). It was found that ectopic expression of AOX from Ciona intestinalis may rescue developmental abnormalities in fruit flies by probable modulation of the c-Jun N-terminal kinase (JNK) signalling pathway (Andjelković et al, 2016).…”
Section: Regenerationmentioning
confidence: 99%
See 1 more Smart Citation